The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1210/jc.2015-4206
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Markers to Predict Conversion From Gestational Diabetes to Type 2 Diabetes

Abstract: The percentage of dimethylation of histones H3K27 and H3K4 varied with diabetic state and has the potential as a predictive tool to identify women who will convert from GDM to type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Women with a history of GDM are at greater risk of developing type 2 diabetes after pregnancy. With this in mind, Michalczyk et al (38) analyzed several epigenetic markers during and after pregnancy in: women with GDM who subsequently developed type 2 diabetes (No. 6); women with GDM who did not develop type 2 diabetes after delivery (No.…”
Section: Epigenetic Studiesmentioning
confidence: 99%
“…Women with a history of GDM are at greater risk of developing type 2 diabetes after pregnancy. With this in mind, Michalczyk et al (38) analyzed several epigenetic markers during and after pregnancy in: women with GDM who subsequently developed type 2 diabetes (No. 6); women with GDM who did not develop type 2 diabetes after delivery (No.…”
Section: Epigenetic Studiesmentioning
confidence: 99%
“…Michalczyk et al. () showed that, on the basis of histone methylation, it is possible to predict the risk of GDM. The results of the study conducted on 39 women suggest that the level of histone H3K27 and H3K4 dimethylation correlates with GDM progression to T2DM.…”
Section: Epigenetics Of Gdmmentioning
confidence: 99%
“…Recent studies have attempted to identify epigenetic biomarkers that can be used to predict the on-set of T2DM following the occurrence of GDM [70][71][72] (Table 1). The studies of Wu et al [70], stand out because they identified maternal DNA methylation changes prior to the diagnosis of GDM; thereby pointing to specific genes (COPS8, PIL3R5, HAAO, CCDC124, and C5 or f34) that may be used as biomarkers for the on-set of GDM prior to its clinical diagnosis.…”
Section: Potential Epigenetic Biomarkers For Predicting Gestational Dmentioning
confidence: 99%
“…The studies of Wu et al [70], stand out because they identified maternal DNA methylation changes prior to the diagnosis of GDM; thereby pointing to specific genes (COPS8, PIL3R5, HAAO, CCDC124, and C5 or f34) that may be used as biomarkers for the on-set of GDM prior to its clinical diagnosis. Studying the epigenetic process of histone methylation, as opposed to DNA methylation, Michalczyk et al [71], studied the blood of GDM versus non-GDM mothers and determined that methylated H3K27 was significantly lower at 8-10 and 20 weeks postpartum in women with GDM who developed T2DM, compared with nondiabetic women. Likewise methylated H3K4 was significantly lower at 8-10 weeks postpartum in women with GDM who later developed T2DM compared with women who had GDM who did later develop the disease.…”
Section: Potential Epigenetic Biomarkers For Predicting Gestational Dmentioning
confidence: 99%